Questões de escrita em textos espontâneos produzidos por estudantes do PROEJA - White, Marlúcia Alves Secundo (2012)
This dissertation is proposed to identify and analyze peculiarities in texts produced by students from PROEJA, Campus Aracaju. The textual production is made up of notes, letters, life stories and opinion pieces, written without teacher guidance. In order to understand the students in this research, it is outlined in the first chapter the history of the deploying this type of education as well as the analysis of the social profile and emphasized the moment these students are exposed to the official language taught at IFS. The theoretical and methodological approach, in the second chapter, substantiates the work with the collective data, as well as individual data. Sociolinguistics is used to analyze the collective data giving the profile of the students involved. For singular data analysis, Evidential Paradigm (cf. Abaurre 1999, 2006) is used since the linguistic data collected not only represent the transposition of speech to writing, but mainly present singularities that give clues about the relationship of the individual with language. The study of speech / writing and individual/ language relationship, in the third chapter, shows that the episodes analyzed are representative of the linguistic variety of languages used by these individuals in their speaking group, but reveals, in a singular manner, the relationship that these individuals keep with the official language imposed upon them by the institution.